Comparative assessment of road traffic noise through 2D noise mapping: A case study of an urban area - Alam, Pervez; Mazhar, Mohd. Aamir; Ahmad, Kafeel; Aslam, Zishan; Afsar, S. S.; Husain, Atif (Frontiers in Sustainability, 2022)
2D noise mapping is an important identification process of locations where noise level may reach to a harmful level, it also provides the propagation of noise in in X and Z direction. Noise pollution has risen to a worrying degree in all zones of the city (residential, commercial, industrial, and silent) because of the rapid rise in urbanization, industrialization, and other connectivity of transport systems in all zones of the city. This comparative analysis of all living area of a city gives clear picture of noise exposure. Thus, the main focus of this study is to carry out comparative analysis of noise exposure level of selected locations such as residential commercial, industrial and silent area of Delhi city using 2D noise maps. Sound Level Meter (SLM) Larson & Davis 831 in compliance with the standard procedure of CPCB is used for monitoring peak traffic hours of working day and night. After that, using sound PLAN (acoustic) and MapInfo Pro, 2-D (Desktop GIS) noise maps were developed, visualized, and analyzed. Residential area is being recorded as maximum noise level followed by commercial and silent zone and the minimum has been observed at industrial area. The high noise level in residential area may be due to heavy traffic volume and road surrounded by high rise buildings. Whereas minimum noise has been observed in industrial area because the industries along the major roads have been surrounded with parapets and trees. As a result, only a small amount of industrial noise entered major highways/roads. Additionally, 2D noise map revealed that the surrounding structures of road (high rise buildings, brick walls, grilled boundaries, trees etc.) significantly influence propagation of noise in all directions..